2020
DOI: 10.1097/ccm.0000000000004123
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Mortality and Health-Related Quality of Life Morbidity Following Community-Acquired Pediatric Septic Shock*

Abstract: Objectives: In-hospital pediatric sepsis mortality has decreased substantially, but long-term mortality and morbidity among children initially surviving sepsis, is unknown. Accordingly, the Life After Pediatric Sepsis Evaluation investigation was conducted to describe the trajectory of mortality and health-related quality of life morbidity for children encountering community-acquired septic shock. Design: Prospective, cohort-outcome study, conducted 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
138
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 37 publications
7
138
1
2
Order By: Relevance
“…Also, a majority (61%) of our patients had a chronic disease, a risk factor for increased mortality from septic shock 44 . This frequency of chronic illness aligns with other reports finding rates of 40-70% of patients admitted to the PICU having a chronic illness 45,46 .…”
Section: Discussionsupporting
confidence: 91%
“…Also, a majority (61%) of our patients had a chronic disease, a risk factor for increased mortality from septic shock 44 . This frequency of chronic illness aligns with other reports finding rates of 40-70% of patients admitted to the PICU having a chronic illness 45,46 .…”
Section: Discussionsupporting
confidence: 91%
“…After implementation, we found that many patients in our program had new difficulties impacting their quality of life after sepsis, which is consistent with research studies reporting new morbidities and impacts on HRQL in children after sepsis (4)(5)(6)(7)(8)(9)(10)(11)20). Based on prior literature, we anticipated more difficulties in psychosocial domains rather than physical functioning (20); however, only one patient reported difficulties with attention, focus, and completion of school activities.…”
Section: Discussionsupporting
confidence: 85%
“…Over one-third of pediatric sepsis survivors have been reported to have new disability one to three months after sepsis diagnosis (4,6), with physical effects and behavioral impacts lasting years in meningococcal sepsis (9,10). In a multicenter, prospective study of health-related quality of life (HRQL) after communityacquired pediatric septic shock, over one-third of children surviving to hospital discharge had deterioration in HRQL on an in-depth assessment 1 year after hospital discharge (11). The largest decrease was seen in the first month after discharge with 50% of survivors below baseline HRQL, with some recovery that plateaued between 3 months and 1 year after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the relevance of long‐term outcomes beyond the hospitalization of children with sepsis received increasing attention. Of concern, more than one‐third of pediatric survivors had not regained their baseline health‐related quality of life one year after an episode of community‐acquired sepsis 95 . Lower quality‐of‐life scores were associated with multiorgan dysfunction, renal replacement therapy, ECMO or cardiopulmonary resuscitation, and duration of mechanical ventilation and inotropes 96 .…”
Section: Discussionmentioning
confidence: 99%